The Welfare of Sheep - Dwyer, Cathy; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
The welfare of the sheep has received less attention than the welfare of intensively husbanded animals. However, domestic sheep may be kept under conditions that are very different from the environment in which wild sheep live, with adverse effects on their behaviour and welfare. This book, written by leading researchers from Europe and Australia, takes a multidisciplinary approach to focus on the specific welfare challenges facing the sheep. The book begins with a discussion of current welfare thinking and how this might be relevant to sheep husbandry. The adaptations of wild sheep to diverse environments, and how their behaviour and physiology has developed to deal with these conditions is described and compared to conditions in modern sheep husbandry. The varied welfare demands of disease, nutrition and metabolism, farming systems and management practices are then discussed by specialists in those areas. The book concludes by considering the economics of improved welfare, and by describing breeding goals and new challenges and opportunities for good sheep husbandry. This book will be of interest to students and academics in animal welfare, animal production, and veterinary medicine, and those with a particular interest in or concern for sheep.
to Animal Welfare and the Sheep -- Environment and the Sheep -- Behaviour and the Welfare of the Sheep -- Sheep Senses, Social Cognition and Capacity for Consciousness -- The Impact of Disease and Disease Prevention on Welfare in Sheep -- Farming Systems for Sheep Production and Their Effect on Welfare -- Nutrition and the Welfare of Sheep -- The Management of Sheep -- The Economics of Sheep Welfare -- Sheep Welfare: A Future Perspective.
Keywords: Zoology; Animal genetics; Animal physiology; Behavioral sciences; Veterinary medicine; Zoology; Animal Genetics and Genomics; Animal Physiology; Behavioral Sciences; Veterinary Medicine/Veterinary Science